The effect of phenylephreni and ephedrine in fetal outcome in the treatment of hypotension during spinal anaesthesia for caesarean delivery - Hamid, Azhari (2006)
Background: Sympathetic blockade manifested by hypotension is one of the most common complications of the regional anaesthesia in obstetric patients. Its prophylaxis and treatment are primarily directed towards the concern that hypotension may result in decreased utero placental perfusion, thus compromised fetus and maternal. Various drugs and methods have been used in attempts to attenuate this response but all have limitations. Many studies using phenylephrine or ephedrine as a prophylaxis drug to suppress these reflexes had shown promising results and reduce the occurrence of fetal acidosis. As both phenylephrine and ephedrine had rapid onset and short duration of action, we formulated a comparative study to evaluate the capability of this drug to reduce the fetal acidosis in the treatment of hypotensive response to spinal anaesthesia. Objectives: The objectives of this double-blinded, randomized study were to compare the fetal outcome after given phenylephrine or ephedrine as a treatment of hypotension in spinal anaesthesia during caesarean delivery. Methods: Fifty four patients, ASA physical status I or ll, undergoing elective lower segment caesarean section surgery were assigned randomly in a double blind, to receive bolus dose of either ephedrine (6mg/ml) or phenylephrine (200mcg/ml), given intravenously asa treatment of hypotension post spinal anaesthesia Heart rate (HR.), systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) were recorded prior to spinal anaesthesia as baseline To and every minute after spinal anaesthesia untill delivery of the fetus. At delivery, the umbilical artery blood was obtained and acid base analysis performed. Apgar scores at 1 and 5 min after delivery was recorded. Patients were also monitored for complications such as nausea, vomiting and arrhythmia. Results: Both ephedrine and phenylephrine groups showed the increase of SBP, DBP and MAP in the treatment of hypotension. Phenylephrine group showed mean umbilical artery pH 7.314 when compared to ephedrine (control) group 7.279. The entire increased in umbilical artery pH was significant statistically. Total overall complications were also significantly lower in phenylephrine group when compared to ephedrine (control) group. Conclusion: Phenylephrine was able to increase the mean fetal umbilical artery pH in the treatment of hypotension in post spinal anaesthesia patients when compared to ephedrine (control) group. The total complications also were lower in patients treated with phenylephrine.